Pengaruh Sistem Pelaporan Keuangan, Pendidikan dan Pengalaman Kerja Terhadap Kualitas Laporan Keuangan - Muhammad Randa Maulid; Linda Linda; Gamal Batara; Raida Fuadi (Akuntabilitas, 2022)
This study aims to analyze the effect of the use of SIMDA – local government management information system, government staff education level, and work experience on the quality of local government financial reports at SKPK (Working Units) in Aceh Jaya District. The population in this study is the ASN (Civil Servants) at SKPK (working units) in Aceh Jaya District, which consists of 43 SKPK. Samples consist of the Head of Finance Division and one of his/her staff from each SKPK. This study found the use of SIMDA and government staff education level do not affect the quality of financial report, while work experience affects the quality of financial report. They face many obstacles on using SIMDA and addition, only 39% of respondents have accounting education background. This shows that the work experience of ASN Aceh Jaya regency is very helpful in improving the quality of financial reports